2010
DOI: 10.1103/physrevb.82.092501
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of the channel-corrected-T-matrix and anomalous-propagator approaches to condensation

Abstract: Any many-body approximation corrected for unphysical repeated collisions in a given condensation channel is shown to provide the same set of equations as they appear by using anomalous propagators. The ad hoc assumption in the latter theory about nonconservation of particle numbers can be released. In this way, the widespread used anomalous-propagator approach is given another physical interpretation. A generalized Soven equation follows which improves a chosen approximation in the same way as the coherent-pot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The GF approximation satisfies both Baym-Kadanoff conditions. 41 The triplet channel in our theory is the same as in the GF theory, and therefore satisfies (23)(24) and (25). We thus focus on the singlet channel in which the RSC theory differs from the GF approximation.…”
Section: B Two-particle Green Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…The GF approximation satisfies both Baym-Kadanoff conditions. 41 The triplet channel in our theory is the same as in the GF theory, and therefore satisfies (23)(24) and (25). We thus focus on the singlet channel in which the RSC theory differs from the GF approximation.…”
Section: B Two-particle Green Functionmentioning
confidence: 99%
“…Though conditions (23)(24)(25)(26) provide in the equilibrium case only limited indication of the validity of full conservation laws, it is significant that the RSC theory passes this test; one can easily show that the other theories we have mentioned fail to satisfy the BK conditions even in equilibrium. For example, the KM approximation does not satisfy the Baym-Kadanoff criterion (26).…”
Section: A Baym-kadanoff Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently it has been shown that one can arrive at the same equations by a completely conserving theory of multiple corrected T‐matrix [ 56–58 ] with equivalent results. [ 59,60 ] This illustrates that the anomalous propagators are a theoretical shortcut to the right result through adopting inconsistent propagators.…”
Section: Introductionmentioning
confidence: 99%